College Expectations Promote College Attendance: Evidence From a Quasiexperimental Sibling Study. (August 2019) - Brumley, Lauren D.; Russell, Michael A.; Jaffee, Sara R.
When adolescents are asked how likely they think it is that they will go to college, does their answer influence what they will actually do? Typically, it is difficult to determine whether college expectations promote academic achievement or just reflect a reasonable forecast of what is likely to happen to them. We used a sample of siblings from the National Longitudinal Study of Adolescent to Adult Health ( N = 1, 766) to test whether associations between college expectations and educational attainment remained after accounting for unobserved family factors that may shape both educational expectations and attainment. Compared with their siblings, adolescents with higher college expectations were also 43% more likely to attend college, even when analyses controlled for grades and IQ. The effect of college expectations on college attendance was strongest among youths living in higher-socioeconomic-status families.